Mapping separase-mediated cleavage in situ. Issue 4 (18th November 2022) - Boukaba, Abdelhalim; Wu, Qiongfang; Liu, Jian; Chen, Cheng; Liang, Jierong; Li, Jingjing; Strunnikov, Alexander V
Abstract: Separase is a protease that performs critical functions in the maintenance of genetic homeostasis. Among them, the cleavage of the meiotic cohesin during meiosis is a key step in producing gametes in eukaryotes. However, the exact chromosomal localization of this proteolytic cleavage was not addressed due to the lack of experimental tools. To this end, we developed a method based on monoclonal antibodies capable of recognizing the predicted neo-epitopes produced by separase-mediated proteolysis in the RAD21 and REC8 cohesin subunits. To validate the epigenomic strategy of mapping cohesin proteolysis, anti-RAD21 neo-epitopes antibodies were used in ChIP-On-ChEPseq analysis of human cells undergoing mitotic anaphase. Second, a similar analysis applied for mapping of REC8 cleavage in germline cells in Macaque showed a correlation with a subset of alpha-satellites and other repeats, directly demonstrating that the site-specific mei-cohesin proteolysis hotspots are coincident but not identical with centromeres. The sequences for the corresponding immunoglobulin genes show a convergence of antibodies with close specificity. This approach could be potentially used to investigate cohesin ring opening events in other chromosomal locations, if applied to single cells.